Penerapan Six Sigma Untuk Penyelenggaraan Ujian Akhir Nasional SMU Di Lima Wilayah DKI Jakarta - Prayekti –; Hanafi – (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikbudristek, 2010)
This paper discusses the results of research on the application of Six Sigma at the junior national exam in Jakarta. This research was conducted on the implementation of the national exam in academic year 2007/2008 Jakarta using survey questionnaire methods in five areas of Jakarta. Questionnaires distributed to students, teachers and supervisors of national examinations. Data were analyzed based on Six Sigma, which has four areas which include quality planning, quality control, quality assurance and quality improvement. result that all schools have generally been preparing themselves before the national exams. Each school has a special program for students to national exam. The program, among others, provide additional educational materials outside lesson time, an extra studying on Saturday and Sunday. To control the quality of each school formed a special committee chaired by the principal. Because the national exam and the estuary is an important activity of all school activities that have been fostering student for six semesters. National exam to measure the success of the school so that the quality coaching to the students to become primary. If you need to be improved in order to be better. From the students, all students are required to follow all the final semester of the program established by school. Therefore, all students are ready for facing a national exam. Graduation rate of students on national exams students did not disappoint, generally in accordance with the expectations of students, parents, teachers and schools.Â ABSTRAKTujuan penulisan artikel ini dimaksudkan untuk membahas hasil penelitian tentang penerapan Six Sigma pada ujian nasional SMU di Jakarta. Penelitian ini dilaksanakan pada ujian nasional tahun ajaran 2007/2008 di Jakarta dengan menggunakan metode kuesioner survei di lima wilayah Jakarta. Kuesioner disebarkan kepada peserta didik, guru dan pengawas ujian nasional. Sekolah yang menjadi sampel masing-masing wilayah lima sekolah negeri dan swasta. Data dianalisis dengan berpedoman pada Six Sigma yang memiliki empat kegiatan,yaitu perencanaan kualitas (quality planning), pengendalian kualitas (quality control), jaminan kualitas (quality assurance) dan peningkatan kualitas (quality improvement). Hasil penelitian menunjukkkan bahwa semua sekolah pada umumnya telah mempersiapkan diri sebelum menghadapi ujian nasional. Setiap sekolah telah membuat program khusus untuk peserta didik yang akan mengikuti ujian nasional. Program tersebut antara lain: memberikan tambahan materi pelajaran di luar jam pelajaran dan tambahan belajar pada hari Sabtu dan Minggu. Untuk pengendalian kualitas setiap sekolah membentuk panitia khusus yang diketuai kepala sekolah. Ujian nasional menjadi tolok ukur keberhasilan sekolah, sehingga kualitas pembinaan kepada peserta didik menjadi prioritas.